PERAN RUANG DIGITAL SEBAGAI MEDIUM PEMBELAJARAN DALAM MENINGKATKAN LITERASI AGAMA GENERASI Z - Arif Fikri; Desi Fitri Efendy; Siti Rahma Duyun; Eby Laila Zannah (Yayasan Baitul Hikmah al-Zain, 2026)
Abstract The advancement of digital technology has transformed social media into an alternative learning space for Generation Z, particularly in supporting the development of religious literacy within an educational context. This qualitative descriptive study aims to explore how social media functions as a learning resource that contributes to the strengthening of students’ religious literacy. Data were obtained through in-depth interviews, observations of educational–religious content across various digital platforms, and online documentation. The findings reveal that social media provides fast, accessible, and interactive religious learning materials that complement formal education. However, challenges arise from the circulation of misinformation, the emergence of unverified religious authorities, and the polarization of religious identity among youth. This study highlights the importance of strong digital literacy skills and pedagogical guidance to ensure that social media is effectively utilized to enhance religious literacy development among Generation Z learners. Keywords: media, religious, literacy, learning, Generation Z.